PUBLIC HEALTH COUNSELING THROUGH THIBBUN NABAWI TREATMENT IN DRAMAGA VILLAGE, DRAMAGA DISTRICT, BOGOR REGENCY - Ginanjar, Muhammad Hidayat; Arijulmanan, Arijulmanan; Sarifudin, Sarifudin; Minanto, Andi; Anas, La (Khidmatul Ummah: Jurnal Pengabdian Kepada Masyarakat, 2024)
The ultimate goal of any development boils down to improving the quality of human resources. Human resources are both the subject and object of development, covering the entire human life cycle, from conception to the end of life. In this case, the public health condition is very important to pay attention to, especially by the government and social observers. In this case, efforts are needed to provide alternative solutions that can improve public health, one of which is through direct assistance and counseling to the community and of course coordinating with local government officials and also community leaders in villages and sub-districts. The STAI Al-Hidayah PKM implementation team provides outreach in the field of public health through the practice of Thibbun Nabawi medicine located in Dramaga Village, Dramaga District, Bogor Regency. Some of the service programs include: health education, Thibbunabawi treatment, medical therapy using electricity and leeches, and distribution of basic food packages. The number of participants who received benefits from Thibbunabawi's counseling and treatment services was 61 patients, civilians, village officials and educators. By holding this activity, the target community feels great benefits, especially in terms of maintaining and improving their physical and spiritual health.